2004
DOI: 10.2202/1544-6115.1055
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the Statistical Significance of Changes in Pathway Activity From Gene Expression Data

Abstract: We present a statistical approach to scoring changes in activity of metabolic pathways from gene expression data. The method identifies the biologically relevant pathways with corresponding statistical significance. Based on gene expression data alone, only local structures of genetic networks can be recovered. Instead of inferring such a network, we propose a hypothesis-based approach. We use given knowledge about biological networks to improve sensitivity and interpretability of findings from microarray expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
81
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 0 publications
0
81
0
Order By: Relevance
“…Rahnenführer et al (2004) demonstrated that the sensitivity of detecting relevant pathways can be improved by integrating information about pathway topology. Barry et al (2005) presented a permutation based procedure, called SAFE, that considers the underlying network structure.…”
Section: Introductionmentioning
confidence: 99%
“…Rahnenführer et al (2004) demonstrated that the sensitivity of detecting relevant pathways can be improved by integrating information about pathway topology. Barry et al (2005) presented a permutation based procedure, called SAFE, that considers the underlying network structure.…”
Section: Introductionmentioning
confidence: 99%
“…Several pathway databases such as KEGG (Ogata et al 1999), BioCarta (http://www.biocarta.com), and Reactome (Joshi-Tope et al 2005) currently describe metabolic pathway and gene signaling networks offering the potential for a more complex and useful analysis. A recent technique, ScorePage, has been developed in an attempt to take advantage of these types of data for the analysis of metabolic pathways (Rahnenfuhrer et al 2004). Unfortunately, no such technique currently exists for the analysis of gene signaling networks.…”
mentioning
confidence: 99%
“…An alternative and more successful technique should consider the distribution of pathway genes in the entire list of genes (9)(10)(11)(12) as well as adjust for the correlation structure. In the innovative Gene Set Enrichment Analysis (GSEA) method (13), the following steps are applied: (i) all genes are ranked by using a signal-to-noise ratio; (ii) for each gene set, the distribution of gene ranks from the gene set is compared against the distribution for the rest of the genes by using the enrichment score (ES) based on a one-sided Kolmogorov-Smirnov statistic; (iii) class labels are permuted to generate a null distribution of ES; and (iv) statistical significance of the observed score is assessed for the top-ranking gene set by comparison with the null distribution of maximum scores from each permutation.…”
mentioning
confidence: 99%